A new substituted bis(vic-dioxime) of its mono-and dinuclear complexes - Güngör, O; Canpolat, E; Kaya, M (Polish Chemical Soc, 2003)
9,10-Bis(hydroxyimino)-4,8,11,15-tetra-aza-1,2,17,18-O-di-iso-propylideneoctadecane (H2L) was synthesized by the reaction-of 1,2-O-iso-propylidene-4-aza-7-aminoheptane and anti-dichloroglyoxime in ethanol, containing an excess of NaHCO3 as a buffer to neutralize the HCl formed. The mononuclear metal complexes of this ligand have been synthesized with Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) salts. H2L forms mononuclear complexes [(HL)(2)M] with a metal ligand ratio of 1:2 with M = Co(II).2H(2)O, Ni(II) and Cu(II). Zn(H) and Cd(II) form with H2L complexes [(H2L)(Cl)(2)M], which have a metal-ligand ratio of 1: 1 and a dinuclear complex with UO2(VI). H2L forms the dinuclear complex [(HL)(2)(OH)(2)M-2] with a metal ligand ratio of 1: 1 with M = UO2(VI). Structures of the ligand and its metal complexes were identified by elemental analyses, IR, H-1 and C-13 NMR spectra and thermogravimetric analyses (TGA).
Keywords: vic-dioxime; cobalt(II); nickel(II); copper(II); zinc(II); cadmium(II); and uranyl(VI) complexes